2016
DOI: 10.1111/edt.12299
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injury research: on children or with children?

Abstract: Background and aim It is widely acknowledged that children should participate in healthcare decisions, service development and even setting research agendas. Dental traumatology is a major component of paediatric dentistry practice and research. However, little is known about young patients’ contribution to new knowledge in this field. The aim of the study was to establish the extent to which children are involved in contemporary dental trauma research and to evaluate the quality of the related literature. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 23 publications
0
36
0
2
Order By: Relevance
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, no previous systematic review has investigated the impact of TDI on the OHRQoL of preschool children and their families. The clarification of this issue could contribute to the identification of oral problems that should be prioritized in the planning and definition of cost-effective prevention and treatment strategies on both the individual and collective levels [ 9 , 16 ]. Moreover, such information should be considered in the education and training of healthcare professionals, who should focus primarily on outcomes identified as clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Internal injuries that included severe damage to face, dental injuries, and tracheal injuries sustained through accidents related to unpowered scooters use have been reported although there was no death [10]. A study done in Finland also reported that the majority of their study subjects (69%) sustained fractures, while 26% had injuries that required anesthesia and surgical intervention [11] [12] [13].…”
Section: Severity Of Injuriesmentioning
confidence: 99%